Atomic mechanism of the distribution and diffusion of lithium in a cracked Si anode. (May 2021) - Wang, Chaoying; Zhang, Chao; Xue, Qianli; Li, Chenliang; Miao, Jiaqi; Ren, Pengfei; Yang, Lijun; Yang, Zailin
Abstract: A multi-scale simulation method was used to present atomistic insight into how cracks affect the distribution and diffusion of lithium (Li) in a silicon (Si) anode. The stable positions, binding energies and dynamic properties of Li in a stressed crack were investigated. Compared with defect free crystalline Si (c-Si), the crack supplies more space to accommodate Li. As a result, there are binding energy gradients centered on the crack tip, which allow Li to exist more stably. Moreover, it is kinetically and thermodynamically favored for Li to diffuse into the crack tip but not to diffuse out. On the propagation plane, the crack may provide fast migration paths for Li to diffuse from both sides into the tip. Finally, Li will concentrate and be imprisoned at the crack tip. Therefore, the appearance of cracks may become a factor that limits the charge/discharge rate of Li-ion batteries. Graphical abstract: Image, graphical abstract